The Relationship Between Spiritual Well-Being and Psychological Distress in Indonesian College Students - Devina Terencia Mulholland; Fikrotul Hanifah (MASI Mandiri Edukasi, 2026)
This study addresses the high prevalence of psychological distress among university students in Indonesia and the limited empirical evidence regarding protective psychological resources within a religious–cultural context. The objective of this research is to examine the relationship between spiritual well-being and psychological distress, including its core dimensions of depression, anxiety, and stress. A quantitative approach was employed using a cross-sectional correlational design. Data were collected from 327 undergraduate students via an online survey using the Spiritual Well-Being Scale (SWBS) and the Depression, Anxiety, and Stress Scale (DASS-21). The data were analyzed using Spearman’s Rho correlation technique. The findings demonstrate a strong and statistically significant negative relationship between spiritual well-being and overall psychological distress (ρ = −0.662), indicating that higher spiritual well-being is associated with lower levels of psychological distress. Further analysis revealed that spiritual well-being was most strongly related to depression (ρ = −0.715), followed by anxiety (ρ = −0.618) and stress (ρ = −0.476). These results confirm the role of spiritual well-being as a significant protective factor against psychological distress among Indonesian university students.